2007
DOI: 10.1515/epoly.2007.7.1.1568
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of PVA/Boron Polymer Produced by an Electrospinning Technique.

Abstract: Abstract:In this study, poly(vinyl alcohol) were cross-linked with boron in varying concentrations and blend fibers were obtained with diameters ranging from 0.3 μ to 4.0 μm with the use of electrospinning process. The resulting product was characterized by SEM, DSC, and FT-IR techniques. There is no beading tendency in either boron doped or undoped fibers. When the amount of boric acid in PVA solutions was increased the conductivity of the polymer decreased. The data indicated the existence of boron oxide in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 4 publications
4
25
0
1
Order By: Relevance
“…The T m for boron doped PVA/Zr‐Y acetate nanofibers disappeared probably due to the crosslinking of PVA with boron and forming an amorphous structure. This shows that crosslinking decreases the degree of crystallinity which is in good agreement with literature [22].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The T m for boron doped PVA/Zr‐Y acetate nanofibers disappeared probably due to the crosslinking of PVA with boron and forming an amorphous structure. This shows that crosslinking decreases the degree of crystallinity which is in good agreement with literature [22].…”
Section: Resultssupporting
confidence: 92%
“…As can be observed, both boron doped and undoped samples have approximately the same spectrum and peaks at about 3361, 2939, 1710, 1567, 1447, 1335, 1096, 850, 657 cm −1 that the effect of PVA is dominant over all the spectra. These peaks are in good accordance with literature [21, 22]. Moreover, previous studies are shown that after calcinations at 500°C, the intensity of those peaks due to PVA are decreased or almost disappeared, indicating the removal of PVA molecules from the fibers [23–25].…”
Section: Resultssupporting
confidence: 91%
“…Among the various polymers, polyvinyl alcohol, polyaniline, poly(alkylthiophene) polypyrrole, polyophene, poly(3-hexylthiophene) became an attractive research topic due to their potential applications and interesting properties by chemists, physicists and electrical engineers alike. Especially, PVA nanofabrics have attracted much attention for decades due to its unique chemical and physical property as well as its industrial application [16][17][18][19][20][21][22][23][24]. The PVA used in this study was selected because of its ease of processing, cost and compatibility with Si.…”
Section: Introductionmentioning
confidence: 99%
“…This process set up consists of four major components: the high-voltage power supply, the spinneret, the syringe pump and the electrically conductive collector. Syringe pump is one of the important components of the process to achieve a constant and adjustable feeding rate of the polymeric solution [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Considering these advantages, nanofibers can find wide applications in various areas such as filtration, optical and chemical sensors, electrode materials, biological and engineering scaffolds, catalyst supports and drug delivery systems [4][5][6][7][8] . Polyvinyl alcohol (PVA) is a water-soluble polymer used in fabrication of polymeric fibers due to its excellent chemical and physical properties, non-toxicity, process ability, good chemical resistance, complete biodegradability, etc 9 . Main parameters which are known to affect the electrospinning process are specific solution properties such as the type of polymer, polymer solution concentration, viscosity, surface tension, electrical conductivity, electrical field strength, fluid flow rate and environmental humidity [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%